2016
DOI: 10.1088/1748-6041/11/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and anti-osteoporotic effects of risedronate-added calcium phosphate silicate cement

Abstract: Osteoporosis greatly impairs bone fracture restoration with bone cement because the accelerated resorption decreases the osseointegration between bone and implants. In this study, we designed a new drug delivery system based on the third generation bisphosphonate risedronate (RA) and the osteogenic calcium phosphate silicate cement (CPSC). The impact of RA on CPSC's material properties and microstructure was evaluated by different characterization methods (μCT, XRD, FTIR, SEM and gas sorption). In addition, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…To achieve it, we used qualitative macroscopic and histological assessments of articular cartilage knee and synovial membrane in non-calcified samples, as well as, a high-resolution micro-CT scanner to evaluate the three-dimensional microstructure and volume of subchondral bone plate, trabecular bone, and osteophyte formation. Risedronate have been extensively studied in rabbit preclinical models in order to evaluate their structural and osteogenic effects as antiresorptive agents ( 54 58 ). Additionally, as previously reported, their effects against osteoarthritic changes on synovial joint tissues were also analyzed in this animal model ( 23 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve it, we used qualitative macroscopic and histological assessments of articular cartilage knee and synovial membrane in non-calcified samples, as well as, a high-resolution micro-CT scanner to evaluate the three-dimensional microstructure and volume of subchondral bone plate, trabecular bone, and osteophyte formation. Risedronate have been extensively studied in rabbit preclinical models in order to evaluate their structural and osteogenic effects as antiresorptive agents ( 54 58 ). Additionally, as previously reported, their effects against osteoarthritic changes on synovial joint tissues were also analyzed in this animal model ( 23 26 ).…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 143 CPCs have been used as drug carriers for antibiotics 144 as well as anti-cancer, 145 anti-inflammatory, 146 and anti-resorptive (anti-osteoporotic) drugs. 147 CPCs have also been used as drug carriers for therapeutically active proteins or growth factors that foster local bone generation. 148 Recently, ionically modified CPCs (for example, with Sr 2+ , SiO 4 4− , Zn 2+ , Mg 2+ ) with the capability of influencing bone modeling and remodeling processes were investigated.…”
Section: Cpc Scaffold Constructs For Bone Tissue Engineeringmentioning
confidence: 99%
“…Gong et al functionalized a calcium silicate powder (CPCS) with 0.5% risendronate (RA) obtaining an increased bone formation in the defects treated with RA-CPCS 0.5%, in comparison with the ceramic material alone and a preventive effect on bone resorption. In addition, the authors found a significantly up-regulation of several genes related to osteogenesis in comparison to CPCS group [51].…”
Section: Medium Animal Modelmentioning
confidence: 89%
“…ALN, RA or ZOL), the major class of antiresorptive drugs used in clinics to inhibit bone loss thus preventing fracture occurrence. In fact, the local use of BPs is adopted to increase bone density preventing bone loss thank to its anti-resorptive capacity and seems to have also a positive effect in modulating the timing of ceramic dissolution, which influences not only bone growth but also the release of loaded drugs or molecules [51,52,62,[86][87][88][89].…”
Section: Discussionmentioning
confidence: 99%